Characterization of microparticles in patients with venous malformations of the head and neck. (18th October 2016) - Zhu, J‐Y; Ren, J‐G; Zhang, W; Wang, F‐Q; Cai, Y; Zhao, J‐H; Chen, G; Zhao, Y‐F
Abstract : Objectives: To determine the basic biochemical features of microparticles (MP) in patients with venous malformation (VM) of the head and neck. Methods: Microparticles were isolated from peripheral venous blood of VM patients or healthy subjects and from lesional fluid of VM patients. Flow cytometry and real‐time polymerase chain reaction were employed to determine the concentration, cellular origin, and RNA expression of obtained MP. A functional coagulation test was applied to measure the coagulant activity of MP. Results: Circulating levels of total MP, platelet‐derived MP, and endothelial MP were significantly elevated in VM patients and were consistently increased in VM patients with more extensive lesions. Lesional MP (MP from lesional fluid of VM) in VM patients were more abundant than circulating MP from VM patients or healthy subjects. Moreover, MP from VM patients displayed markedly distinct mRNA and microRNA expression compared with healthy subjects. Furthermore, MP from VM patients exhibited enhanced procoagulant activity, as evidenced by significantly shorter coagulation time. Conclusions: This study demonstrates for the first time that patients with VM have an altered MP profile and MP may be associated with VM‐associated thrombogenesis. Further studies are required to explore the precise pathophysiological roles of MP in VM.